LEMBAGA KONSERVASI SATWA DALAM PERSPEKTIF PERDAGANGAN SATWA ILEGAL - I Gusti Ayu Pradnya Swari Dewi (University of Udayana, 2016)
Indonesia is a country that is very rich its animal diversity, but is also know as a countrythat has a long list of endangered wildlife. The destruction of forests, the transfer function of over-harvesting and the destruction of their habitat is the main factor that threatens the extinction of wildlife. Forests as house a wide variety of wildlife is no longer able to protect the exixtence of wildlife due to habitat destruction. Various rare species endemic in Indonesia such as Sumateran tigers, one-horned rhino, the Javan hawk eagle, dragons, birds of paradise and other animals gravely threatened. Illegal wildlife trade proses a serious threat to the preservation of the wildlife. The wildlife illegally traded most are cought from the wild and not of capativity. By law the government efforts to protect endangered species from extinction is done with the issuance of Law No. 5 of 1990 on Conservation of Natural Resources and ecosystems followedby the enactment of Minister of Forestry Number : P.53/Menhut-II/2006 on Conservation. Public education to raise public awareness of the importance of wildlife conservation play an important role in wildlife conservation. Institutions ex-situ conservation becomes a toggle while during their forests in the rescue effort should be able to give life maximum for wildlife with regard to ethics and the rules of animal welfare so that the function and purpose of conservation agencies as a place of education, research and development of science can be fixed accomplished. Indonesia merupakan negara yang sangat kaya dengan keanekaragaman satwanya, namun dikenal juga sebagai negara yang memiliki daftar panjang tentang satwa liar yang terancam punah. Perusakan hutan, pengalihan fungsi hutan yang berlebihan serta rusaknya habitat mereka merupakan faktor utama yang mengancam punahnya satwa liar tersebut. Hutan sebagai rumah berbagai macam satwa liar tidak lagi mampu melindungi keberadaan satwa akibat perusakan habitatnya. Berbagai satwa endemik yang langka di Indonesia seperti harimau Sumatera, badak bercula satu, elang jawa, komodo, burung cendrawasih dan satwa-satwa lainnya keberadaannya terancam punah. Secara hukum upaya pemerintah dalam melindungi satwa langka dari ancaman kepunahan dilakukan dengan dikeluarkannya Undang-Undang Nomor 5 Tahun 1990 tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya selanjutnya diikuti dengan ditetapkannya Peraturan Mentri Kehutanan Nomor : P.53/Menhut-II/2006 tentang Lembaga Konservasi. Edukasi kepada masyarakat untuk meningkatkan kesadaran publik akan pentingnya pelestarian satwa liar memainkan peranan penting dalam pelestarian satwa liar. Lembaga konservasi ex-situ menjadi tempat tiggal sementara selama hutan mereka dalam upaya penyelamatan harus mampu memberikan kehidupan yang maksimal bagi satwa liar tersebut dengan tetap memperhatikan etika dan kaidah kesejahteraan satwa sehingga fungsi dan tujuan lembaga konservasi sebagai tempat pendidikan, penelitian dan pengembangan ilmu pengetahuan dapat tetap terlaksana.